Ownership, Board, and Enterprise Risk Management - Otero-González, Luis; Rodriguez-Gil, Luis-Ignacio; Durán-Santomil, Pablo; Tamayo-Herrera, Araceli (European Journal of Family Business, 2020)
This paper analyses the effect of family ownership and the characteristics of the board of directors on the implementation level of enterprise risk management (ERM) in Spanish non-financial companies. The sample consists of 162 Spanish non-financial companies listed on Spanish stock exchanges and markets during 2012–2015. The results obtained show that the relationship between the level of family ownership concentration and the implementation level of an ERM system has a non-linear structure. Therefore, a reduction in implementation for moderate ownership levels is observed, although this increases with high ownership values. Regarding corporate governance, our study confirms the importance of certain characteristics of the board of directors, such as the size and the figure of the shareholder director in the implementation of formal ERM systems.